Political Consciousness Among Dalit and Non-Dalit - Adhikari , Ram Chandra (International Journal of Social Sciences and Management, 2025)
This study examines caste-based discrimination against Dalits in Bharatpur 12, Chitwan district, Nepal, focusing on their social, economic, and political conditions. Data were collected through a survey of Dalit and non-Dalit households using structured questionnaires. The results showed that most household heads were male. Unemployment was higher among Dalits (54.20%) than non-Dalits (45.80%), and more non-Dalits (51.60%) worked in agriculture compared to Dalits (48.60%). Average land ownership was small at 0.14 hectares, and most families were nuclear. Hinduism was the main religion (71.25%), followed by Christianity (16.25%) and Buddhism (12.25%). Mobile phones were the most commonly used communication tool, followed by television (88.75%) and social media (70.00%). Participation in political campaigns was low, especially among Dalits. About 90% of respondents said caste did not influence their voting decisions. However, 15% admitted voting for money. Awareness of political agendas was high (70%), and development issues influenced 53.75% of voters. The most important criteria for voting were commitment to development (63.75%), followed by the candidate’s education (25%) and personal relationships (11.25%). Dalits were less consistent in their political preferences, often changing parties based on the performance of candidates and their community’s needs. The findings highlight the ongoing challenges of unemployment, limited resources, and political disengagement among Dalits. Addressing these issues requires focused efforts to improve economic opportunities, increase political participation, and reduce caste-based discrimination Int. J. Soc. Sc. Manage. Vol. 12, Issue-1: 1-8.